P148 The lies we tell – Pre-test probability is only useful at risk stratifying pulmonary emboli when used accurately. (19th November 2012) - Newnham, M; Stone, H; Salehi-Bird, S; Summerfield, R; Mustfa, N
Abstract : Introduction: Pre-test probability (PTP) scores are widely used to risk stratify pulmonary emboli (PE). A multitude of scores exist; however diagnosing PE remains challenging. We aim to identify whether patients were correctly PTP scored and what effect rescoring with the correct information has on predicting PE. We will identify the effect different PTP scores have on the likelihood of PE. Methods: We conducted a retrospective study of inpatient computer tomography pulmonary angiograms (CTPA) within a large teaching hospital over a 1-year period. We recorded the originally submitted PTP score (modified Wells score), D-Dimer result and the CTPA outcome (PE-positive or negative cohorts). The accuracy of the PTP score was assessed from the original clinical information; rescoring when appropriate. We also rescored using alternative PTP systems (Geneva and simplified BTS). We analysed whether any factor or PTP scores could predict the presence of PE. Results: 202 CTPAs were performed (70, 35% PE positive; 131, 65% PE negative). Baseline characteristics did not differ (age, gender, requesting team, inflammatory markers, mortality). PE was more likely with a higher D-dimer (682 vs. 853; p<0.001); pneumonia occurred more frequently in the PE-negative cohort (61 vs. 12; p<0.001). A third of forms were scored incorrectly; occurring significantly more in the PE-negative cohort (p=0.001). There was no difference between the original PTP scores (3.7 vs. 3.8; p=0.631); however when rescored with the correct clinical information, the PE-positive cohort had a significantly higher PTP score (2.0 vs. 3.1; p=0.001) ( Table 1 ). Geneva score did not accurately predict PE (2.3 vs. 2.5; p=0.25); whereas the simplified BTS score did (0.9 vs. 1.3; p<0.001). Conclusions: Patients without a PE were significantly more likely to have an incorrect PTP score. Clinicians may have poor concordance with scoring to meet CTPA requesting criteria. The originally calculated PTP score was not predictive of PE. However, when scores were adjusted with the correct information, a higher PTP score was predictive of PE. Simple PTP scoring systems performed well compared with more complex versions. PTP scores are only effective at predicting PE when used accurately; this may not occur in practise.